Tribo-electrochemical behavior of bio-functionalized TiO2 nanotubes in artificial saliva: Understanding of degradation mechanisms - Alves, Sofia A. [UNESP]; Rossi, André L.; Ribeiro, Ana R. [UNESP]; Toptan, Fatih; Pinto, Ana M.; Celis, Jean-Pierre; Shokuhfar, Tolou; Rocha, Luís A. [UNESP] (Elsevier, 2017)
It has been shown that the synthesis of TiO2 nanotubes by anodization provides outstanding properties to Ti surfaces intended for dental and orthopedic implants applications. Beyond the very well-known potential of these surfaces to improve osseointegration and avoid infection, the knowledge on the adhesion and degradation behavior of TiO2 nanotubes under the simultaneous action of wear and corrosion is still poorly understood and these are issues of tremendous importance. The main aim of this work is to investigate, for the first time, the tribo-electrochemical degradation behavior of Ti surfaces decorated with TiO2 nanotubes before and after bio-functionalization treatments. Well-aligned TiO2 nanotubes (NTs) were produced containing elements natively present in bone such as calcium (Ca) and phosphorous (P), in addition of zinc (Zn) as an antimicrobial agent and stimulator of bone formation. The synthesis of Ca/P/Zn-doped nanotubes (NT-Ca/P/Zn) was achieved by reverse polarization and anodization treatments applied to conventional TiO2 nanotubes grown by two-step anodization. The nanotube surfaces were analyzed by scanning electron microscopy (SEM) while dark-field scanning transmission electron microscopy (STEM-DF) was used to characterize the Ti/TiO2 nanotubular films interfaces. Tribo-electrochemical tests were conducted under reciprocating sliding conditions in artificial saliva. The open circuit potential (OCP) was monitored before, during and after sliding tests, and the coefficient of friction (COF) values were registered during rubbing action. The wear tracks resulting from sliding tests were characterized by SEM and wear volume measurements were carried out by 2D profilometry. The results show that the tribo-electrochemical behavior of TiO2 nanotubes was significantly improved after bio-functionalization treatments. The higher electrochemical stability and lower mechanical degradation of these films was correlated with their improved adhesion strength to Ti substrate, which is granted by the nano-thick oxide film formed at the interface region, during bio-functionalization processes. A first insight on the degradation mechanisms taking place during tribo-electrochemical action is proposed. The outcomes of this study may contribute in a great extent for the development of new implant surfaces with improved biomechanical stability and thus contribute for the long term success of dental implants.
Keywords: Bio-functionalization; Dental implants; Film adhesion; TiO2 nanotubes; Tribocorrosion